2017
DOI: 10.5098/hmt.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Water Transportation in Nanochannel

Abstract: The flow factor approach model was used to study the effect of temperature on water transportation in a nano slit pore flow driven by the pressure. The influences of the temperature on the density and viscosity of water and on the water-wall interaction were considered. The results show that enhancing the temperature of water significantly improves water transportation in nanochannel, especially when the channel height is so low that the water non-continuum effect is significant. The mechanism of this temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It was shown that this slow flow is due to the nanoscale pore radius, the increased effective viscosity of the liquid in the confining pores and the significant non-continuum effect of the liquid across the pore radius (Zhang, 2016). It was suggested that increasing the liquid temperature can effectively improve the flow rate through nanoscale pores (Zhang, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this slow flow is due to the nanoscale pore radius, the increased effective viscosity of the liquid in the confining pores and the significant non-continuum effect of the liquid across the pore radius (Zhang, 2016). It was suggested that increasing the liquid temperature can effectively improve the flow rate through nanoscale pores (Zhang, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the temperature of water affects the thermal distribution of the water molecules and the stability of the hydrogen-bond network. The change of the temperature can have impact on both the static and dynamic characteristics of water, such as significantly faster water transport at higher temperature in nanochannels [13], much slower dynamics in monolayer water than those in a fully hydrated pore at ambient temperatures but the opposite at low temperature [14], and slightly higher absorbance near 3350 cm −1 for bulk water at a lower temperature [15,16]. Another example is that the temperature dependence of water dynamics shows a weak crossover from fragile behavior to strong behavior in the hydration shells of elastin-like and collagen-like peptides [17].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the temperature of water affects the thermal distribution of the water molecules and the stability of the hydrogen-bond network. The change of the temperature can have an impact on both the static and dynamic characteristics of water, such as significantly faster water transport at higher temperatures in nanochannels, much slower dynamics in monolayer water than those in a fully hydrated pore at ambient temperatures but the opposite at low temperatures, and slightly higher absorbance near 3350 cm –1 for bulk water at a lower temperature. , Another example is that the temperature dependence of water dynamics shows a weak crossover from fragile behavior to strong behavior in the hydration shells of elastin-like and collagen-like peptides . These interesting phenomena show that the temperature can be taken as a sensitive parameter to modulate the hydrogen-bond network and affect the properties of water.…”
Section: Introductionmentioning
confidence: 99%